Alternative Management Approaches of Citrus Diseases Caused by Penicillium digitatum (Green Mold) and Penicillium italicum (Blue Mold) - Bhatta, Usha K. (Frontiers in Plant Science, 2022)
Green mold (Penicillium digitatum) and blue mold (Penicillium italicum) are among the most economically impactful postharvest diseases of citrus fruit worldwide. Postharvest citrus diseases are largely controlled with synthetic fungicides such as pyrimethanil, imazalil, fludioxonil, and thiabendazole. Due to their toxic effects, prolonged and excessive application of these fungicides is gradually restricted in favor of safer, more eco-friendly alternatives. This review comprehensively describes alternative methods: (a) biocontrol agents, (b) plant extracts and essential oils, (c) bio fungicides, (d) chitosan and chitosan derivatives, (e) heat treatments, (f) ionizing and nonionizing irradiations, (g) food additives and generally regarded as safe (GRAS) salts, and (h) synthetic elicitors, for the control of P. digitatum and P. italicum. Integrating treatment approaches such as biocontrol agents with food additives and GRAS salts or heat treatments has overcome some drawbacks to single treatments. In addition, it may also produce an additive or synergistic effect on controlling both molds for a satisfactory level of disease reduction in postharvest citrus. Further research is warranted on plant resistance and fruit-pathogen interactions to develop safer strategies for the sustainable control of P. digitatum and P. italicum.